Avaliação de eficiência da operação de foguetes de sondagem: uma abordagem com network DEA e teoria dos jogos - Gomes, Hareton Ribeiro (2021)
This research aimed to propose a methodology to evaluate the efficiency of the Sounding Rocket Launch Operation (SRLO) through Network Data Envelopment Analysis (NDEA) and game theory, for suborbital rockets, launched at from a launcher with an inclined ramp, with the adjustment parameter, the calculation of ballistic wind for the launch region, in order to allow SRLO managers to make their decisions based on benchmarking analysis, since there is a lack of efficiency analysis on rockets and SRLO. Investments in the Brazilian aerospace sector become more contingent due to the country's current economic scenario. This requires the brazilian aerospace sector to optimize its financial resources, therefore the need for the better use of these resources, and consequently, an increase in the efficiency of the internal processes of its executing agencies, become indispensable to achieve the economic and financial results desired by the country. In this context, the measurement and improvement of the SRLO efficiency of the brazilian launch fields made it possible, in addition to providing better services to the Center's customers, a better allocation of resources and increased productivity, in an increasingly competitive and super-specialized sector. The research on SRLO will have a time frame from 2009 to 2019 in the launches of space vehicles of the training rockets project launched from the Barreira do Inferno Launch Center (CLBI- Centro de Lançamento da Barreira do Inferno) observing 24 launches. From this analysis, the results show that there was high efficiency of launches in the Launcher Adjustment Stage (LAS) with an average of 75.40% due to the OLFS control actions performed by the launch center team at this stage and a very low Efficiency in launches in the Atmospheric Flight Stage (AFS) with an average of 13.50%, due to the interference of exogenous factors in the SRLO process at this stage, mainly from the launch field atmosphere, so the average global efficiency of launches was of 9.80%, a value close to the efficiency of the AFS stage. This new approach sought to answer how a mathematical technique can help suborbital launch field managers' decision making.